Efektivitas Ketersediaan Air Irigasi untuk Kebutuhan Air Tanaman Padi Di Desa Senaro Kecamatan Purwodadi Kabupaten Musi Rawas - RA. Sri Martini; Erny Agusri; Indri kusuma Dewi (Jurnal Tekno Global, 2021)
The Availability of water for irrigation purposes can be broadly divided into two types, namely the availability of water in the land and availability of water in take buildings. The availability of irrigation water both on land and in buildings is expected to meet the need of making irrigation water needed in irrigation areas were reviewed in accordance with its area and cropping patterns that exist. The research done is to calculate the availability of irrigation water, the water requirement of rice plants and distribution efficiency. To calculate availability and water requirements of rice plants needed data as a reference, namely data from the Meteorology and Geophysics Musi rawas district , while to analyze the efficiency of distribution used discharge data measured by the method of floating then compared the results of discharge at the beginning and the discharge end of the channel. The results of calculations and measurements, availability of water in the Senaro Village can be fulfilled It can be seen from the average availability, in the first planting season (September to Januari) average of 0,92 m3/sec with an average water demand for -0,04 m3/sec and the second planting season (Januari toMei) average of 0,47 m3/sec with an average water demand of 0,04m3/sec. As for the value of the efficiency of each tertiary channel in Senaro village is 1-4m ka has efficiency values of 91%, 2-4m ka has efficiency values of 86% ,3-4m ka has efficiency values of 74% 4-4m ka has efficiency value of 64%. 5-4m ka has efficiency value of 72%.  Keywords : Availability of Water Irrigation, Water Supplies, Efficiency Distribution